INTERPRETASI GEOLOGI BAWAH PERMUKAAN DAERAH POTENSI MATA AIR PANAS KALIULO KABUPATEN SEMARANG BERDASARKAN DATA GEOMAGNET MENGGUNAKAN MODEL 2-D & 3-D - Diny Agustina Rahayu; Udi Harmoko; Tony Yulianto; Sugeng Widada; Yusuf Dewantoro (Youngster Physics Journal, 2016)
The geothermal hot springs has been discovered in the Kaliulo area, Pringapus district of Semarang Regency. The research was conducted by 2-D and 3-D model geomagnetic for find the geological subsurface structure. Observation data such as magnetic field of 61 point used one set of PPM (Proton Precission Magnetometer) GSM geometrics 19 T and two units Geotron Magnetometer Model Unit G5. Data analysis of geomagnet was undertaken by diurnal correction and IGRF (International Geomagnetic Reference Field) correction to obtain the total of magnetic field anomalies. The total magnetic field anomaly data were utilized to create anomaly contour. That anomaly is used for doing reduction to plansurface process, upward continuation that produce anomalies local and regional, and reduction to pole. Modeling was done on the local magnetic anomalies to review subsurface using Mag2DC and UBC Mag3D. The results showed the + (positive) closure and – (negative) closure that can indicate anomalies object in other word to be weak zone or geological structure of fault is available, so that the slicing is made on that closure. Based on the model 2-D normal fault structure the northwestsoutheast trending and northeast-southwest, this interpreting so that normal faults which controlled source hot springs Diwak to Kaliulo.